Nutrition, diet and cancer - Srivastava, Rakesh K.; Shankar, Sharmila (Springer Netherlands, 2012)
Chemoprevention of cancer has been the focus of intensive research for more than two decades. Epidemiological evidence has shown a small, but significant association between fruit and vegetable intake and a reduction in cancer risk.  Diet may account for about thirty five percent of cancer. Large claims have been made for the effectiveness of particular diets in determining one's risk of developing cancer, ranging from protection against cancer initiation, progression and metastasis. A wide array of dietary components has been demonstrated to be as effective in fighting off cancer. Towards an increased understanding of the nutrition, excercise and diet in preventing cancer or inhibiting its progression has led to the discovery and development of novel and effective drugs that regulate intracellular signaling network in the body.  This information will be very useful to explore novel and highly effective chemopreventive strategies for reducing the health burden of cancer. Hippocrates, who proclaimed 25 centuries ago, 'Let food be thy medicine and medicine be thy food'. They estimated that one third of all cancer cases could be prevented by a healthier diet; statements which are widely accepted in the scientific literature. This book covers the current state-of-the art knowledge on the impact of nutrition and diet with nutrigenetics, nutritional epigenomics, nutritional transcriptomics, proteomics, and metabolomics approach in cancer prevention and therapy.